Rancang Bangun Aplikasi Pengelolaan Marketplace Stikom Surabaya Berbasis Android - Maysaroh, Dita Astrina; Hariadi, Bambang; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
In accordance with the tri dharma of higher education and research, research and development, and community service, lecturers at Stikom SurabayaÂ every year can produce works from research activities. In addition to lecturers, students can also produce works research work from courses and practical work. The work of lecturers and students Stikom Surabaya can have selling points. The establishment of the Marketplace Stikom Surabaya. By being a platform that can accommodate the work of lecturers and students that can help to offer their products. A marketplace requires management to limit the problems that occur. Based on the explanation above, it can be seen that the problems that occur in the Stikom Surabaya marketplace if it does not have good management such as shops making products that are prohibited in the available categories, stores that do not complete transactions and there are buyers who have not confirmed receipt of goods after the goods are taken. Management can also be used to control processes such as transaction processing, entry and exit of marketplace balances, feedback from users, receipt and delivery of goods at distribution points. Based on the existing problems, research will be carried out to design and build an Android-based marketplace management application for Stikom Surabaya. The design and build application marketplace management Stikom Surabaya based android platform that can manage standardization, distribution points, create voucher / promo features, manage premium members, manage complaint resolution, record cash flow, use push notifications in real time, store management in the marketplace, and transaction management so that transactions are monitored. In developing applications, the process of withdrawing balances can be made directly into the seller's account, adding vouchers for reward badges / levels, adding features for premium members, automatically developing checks on the names of products added, and using schedule tasks or the like to inspect goods that have not been taken at the distribution point.